The Temporal Nature of Mobile Push Notification Alerts: A Study of European News Outlets' Dissemination Patterns. Issue 6 (3rd July 2021) - Wheatley, Dawn; Ferrer-Conill, Raul
Abstract: Push notifications provide news outlets with direct access to audiences amid concerns around information overload, disinformation, and heightened competition for reader attention. Such news distribution is relevant because it (a) bypasses social media and news aggregators, reaching readers directly; (b) alters the agency and control of temporal news personalisation; and (c) reinforces mobile as the locus of contact between news organisations and audiences. However, push notifications are a relatively under-researched topic. We explore news organisations' use of alerts, considering whether they attempt to integrate with existing mobile-user behaviour patterns or seek to be a disruptive element, garnering attention when audiences are not typically using devices. Through quantitative content analysis, this study examines the temporality of push notifications ( n  = 7092) from nine Northwestern European countries, comprising 34 news outlets. These data allow for comparisons at two levels: publisher type and national context. The study shows how the temporal patterns of push notifications' dissemination align with existing news consumption behaviours; concepts of content-snacking and audiences' rhythms and rituals are a useful lens through which these immediate, concise texts can be considered. Our findings show that news organisations use the mobile channel for attracting and maintaining users' attention, with varying interpretations of temporal customisability.